Terlalu lucu untuk diingat? Analisis efek humor dalam iklan - Hamdan, Stephani; Srisayekti , Wilis; Lawoto, Amanta Fedora; Arasy, Fadel Putra; Pijoh, Michaela Christy; Yanson , Michelle Atalya (Mediapsi, 2025)
The effectiveness of advertisements depends on their creativity to attract and be remembered by consumers, including the use of humor. Humor can arouse positive emotions that help someone remember more. This study examines the influence of humor in advertising on recall ability. with 75 students taken using simple random sampling technique and compared in two groups: control group (38 participants) and experimental group (37 participants). A post-test involving short-answer questions measures participants' recall abilities. Mann-Whitney analysis indicates no significant difference between the two groups. These results suggest that the inclusion of humor in advertising does not significantly affect recall abilities. This showed that humor in advertisements is not a factor that influences someone to remember more information from an advertisement